Testing the hypothesis that psychotic illness begins when subthreshold hallucinations combine with delusional ideation. (8th June 2012) - Smeets, F.; Lataster, T.; van Winkel, R.; de Graaf, R.; ten Have, M.; van Os, J.
<x xml:space="preserve">Abstract</x> Objective: While hallucinations and delusions are often considered as a single class of 'positive symptoms', little is known about their dynamic cooccurrence in relation to clinical outcome in non‐help‐seeking people. Method: The Netherlands Mental Health and Incidence Study (NEMESIS‐1) is a longitudinal study of mental disorders (n = 7075) with three measurements over a 3‐year period. Risk factors, persistence of psychotic experiences, and clinical outcome were analyzed for groups with: i) no psychotic experiences, ii) only delusions, iii) only hallucinations, and iv) both delusions and hallucinations. Results: Hallucinations and delusions occurred together more often (T0, 3.5%; T1, 1.0%; T2, 0.9%) than that predicted by chance (T0, 1.0%; T1, 0.1%; T2, 0.04%). The group with both symptoms showed more 'first‐rank'‐like delusions compared with the group with only delusions. Having both hallucinations and delusions, compared to isolated symptoms, was associated more strongly with risk factors, comorbid affective symptoms, negative symptoms, and persistence of psychotic experiences. This was not an artifact of having more symptoms in general. Conclusion: Experiencing both delusions and hallucinations is an indicator of greater etiological load resulting in more clinical outcome. A specific 'hallucinatory‐delusional state' may represent an early phase of exacerbation of aberrant attribution of salience, increasing risk for clinical outcome.